1989
DOI: 10.1073/pnas.86.6.2031
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal translocation in a human leukemic stem-cell line disrupts the T-cell antigen receptor delta-chain diversity region and results in a previously unreported fusion transcript.

Abstract: We have studied a leukemic stem-cell line,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(143 citation statements)
references
References 40 publications
2
140
0
1
Order By: Relevance
“…The TAL1 (or SCL) gene was originally identi®ed from its involvement by a recurrent chromosomal translocation in patients with T-cell acute lymphoblastic leukemia (T-ALL) (Begley et al, 1989a;Chen et al, 1990;Finger et al, 1989). Interstitial deletions that fuse TAL1 coding sequences to the promoter of an upstream gene, SIL (for SCL interrupting locus), were found subsequently to occur with greater frequency than translocations (Aplan et al, 1990;Bernard et al, 1990;Brown et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The TAL1 (or SCL) gene was originally identi®ed from its involvement by a recurrent chromosomal translocation in patients with T-cell acute lymphoblastic leukemia (T-ALL) (Begley et al, 1989a;Chen et al, 1990;Finger et al, 1989). Interstitial deletions that fuse TAL1 coding sequences to the promoter of an upstream gene, SIL (for SCL interrupting locus), were found subsequently to occur with greater frequency than translocations (Aplan et al, 1990;Bernard et al, 1990;Brown et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44] However, it has recently been shown that aberrant overexpression of T-ALL oncogenes can occur in the absence of chromosomal translocation. 45 In order to characterize the expression of T-ALL oncogenes, such as scl, lmo1, lmo2, hox11, tlx3a and tlx3b in NOTCH1-induced T-cell leukemias, RT-PCR analysis was performed using oncogene-specific primers with RNA from FACS-sorted GFP-positive leukemic cells.…”
Section: Expression Of Other Known T-all Oncogenes In Notch1-induced mentioning
confidence: 99%
“…[1][2][3][4] Genomic rearrangements of the SCL gene have been reported in approximately 30% of patients with paediatric T-ALL 5,6 and it has been suggested that additional mechanisms may be responsible for ectopic expression in a further 30% of these patients. 4 Transgenic studies in mice have also shown Correspondence: AR Green; Fax: 44 01223 336827 Received 4 September 1998; accepted 20 February 1999 that ectopic expression of SCL in thymocytes gives rise to T cell tumours.…”
Section: Introductionmentioning
confidence: 99%